Use of standard, contact, and droplet precautions with eye protection for the prevention of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) transmission among home healthcare personnel in hospice and home healthcare settings—King and Snohomish counties, Washington, February–October 2020. (10th March 2023) - McMichael, Temet M.; Duca, Lindsey M.; Lewis, James; Riedo, Francis X.; Wilde, Nancy; McDonald, Molly; Spitters, Christopher; Wechkin, Hope A.
Abstract: Among EvergreenHealth Home Care Service professionals, no coronavirus disease 2019 (COVID-19) cases were reported when they were instructed to use standard, contact, and droplet precautions with eye protection while providing home health care to patients diagnosed with laboratory-confirmed severe acute respiratory coronavirus virus 2 (SARS-CoV-2). These precautions might provide some level of protection against coronavirus disease 2019 (COVID-19) among home healthcare personnel.